Comprehensive Tissue-Specific Transcriptome Analysis Reveals Distinct Regulatory Programs during Early Tomato Fruit Development - Pattison, Richard J.; Csukasi, Fabiana; Zheng, Yi; Fei, Zhangjun; Catala, Carmen (Oxford Academy, 2015)
Fruit formation and early development involve a range of physiological and morphological transformations of the various constituent tissues of the ovary. These developmental changes vary considerably according to tissue type, but molecular analyses at an organ-wide level inevitably obscure many tissue-specific phenomena. We used laser-capture microdissection coupled to high-throughput RNA sequencing to analyze the transcriptome of ovaries and fruit tissues of the wild tomato species Solanum pimpinellifolium. This laser-capture microdissection-high-throughput RNA sequencing approach allowed quantitative global profiling of gene expression at previously unobtainable levels of spatial resolution, revealing numerous contrasting transcriptome profiles and uncovering rare and cell type-specific transcripts. Coexpressed gene clusters linked specific tissues and stages to major transcriptional changes underlying the ovary-to-fruit transition and provided evidence of regulatory modules related to cell division, photosynthesis, and auxin transport in internal fruit tissues, together with parallel specialization of the pericarp transcriptome in stress responses and secondary metabolism. Analysis of transcription factor expression and regulatory motifs indicated putative gene regulatory modules that may regulate the development of different tissues and hormonal processes. Major alterations in the expression of hormone metabolic and signaling components illustrate the complex hormonal control underpinning fruit formation, with intricate spatiotemporal variations suggesting separate regulatory programs.
Keywords: Tomates - Evolución; RNA-seq; Tomato; Laser capture; Fruit development